"Going the Extra Mile": Disclosure, Accommodation, and Stigma Management among Working Women with Disabilities. Issue 8 (3rd August 2019) - Moloney, Mairead Eastin; Brown, Robyn Lewis; Ciciurkaite, Gabriele; Foley, Susan M.
ABSTRACT: Although research has quantitatively evaluated the impacts of stigma upon working women with disabilities (WWD), nuanced, qualitative accounts voiced by these women are rare. To address this literature gap, we conducted seven focus groups with 42 WWD. We asked: "What are women's experiences of disability disclosure and accommodation in the workplace?" Findings reveal that WWD face intentional and unintentional structural discrimination and must weigh the pros and cons of disclosure and navigate devaluation threats in pursuing workplace accommodations. "Going the extra mile" emerged as a stigma management technique which was prevalent among women of higher social capital.